Discovering vintage New Orleans : a guide to the city's timeless shops, bars, hotels & more - Stuart, Bonnye E. (Discovering Vintage., 2015)
Discovering Vintage New Orleans is a guide to all of the city's timeless classic spots that take you back in time. The book spotlights the charming stories that tell you what each place is like now and how it got that way. It includes indexes that let you choose the places you want to visit by neighborhood, by category, and-naturally-by era. Discovering Vintage New Orleans takes you to classic restaurants, shops, and other establishments that still thrive today and evoke the unique character of the city. They're all still around-but they won't be around forever. Start reading, and start your d.